The Development of Google Sites-Based Learning Media in Islamic Cultural History Subject at MTsN 1 Langsa - Khairunnisa Khairunnisa; Mohd Nasir; Mulyadi Mulyadi (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study objective is to develop Google Sites–based learning media for the History of Islamic Culture (SKI) subject, evaluate its validity, and analyze the responses of teachers and students regarding its implementation. The study utilized a Research and Development (R&D) methodology, namely the Four-D (4D) model, which encompasses the steps of define, design, develop, and disseminate. The research participants included one materials expert, two media experts, two SKI teachers, and thirty-four seventh-grade students from the Digital class at MTsN 1 Langsa. Data were gathered using validation questionnaires, observations, and interviews, and subsequently analyzed employing both quantitative and qualitative methodologies. The results indicate that the development process was methodically executed in alignment with the 4D model. Expert validation showed that it was very likely to work, with scores of 98.6% from material experts and 95.3% from media experts. Limited testing at the distribution stage showed very positive results, with 94% of students and 97.3% of teachers saying that the media are very useful and good for SKI learning. These findings indicate that Google Sites-based learning media offer a novel and efficacious alternative for SKI instruction in madrasahs, facilitating effective content delivery, augmenting student motivation and learning autonomy, and promoting digital literacy in technology-enhanced learning environments.